2012
DOI: 10.1186/1471-2148-12-80
|View full text |Cite
|
Sign up to set email alerts
|

The mammary gland-specific marsupial ELP and eutherian CTI share a common ancestral gene

Abstract: BackgroundThe marsupial early lactation protein (ELP) gene is expressed in the mammary gland and the protein is secreted into milk during early lactation (Phase 2A). Mature ELP shares approximately 55.4% similarity with the colostrum-specific bovine colostrum trypsin inhibitor (CTI) protein. Although ELP and CTI both have a single bovine pancreatic trypsin inhibitor (BPTI)-Kunitz domain and are secreted only during the early lactation phases, their evolutionary history is yet to be investigated.ResultsTammar E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 97 publications
(220 reference statements)
0
7
0
1
Order By: Relevance
“…Previous examination of mammalian milk proteins revealed that discrete, specific sections of each gene are subject to neutral, negative or positive selection [32] . Using a similar MEGA-based analysis to specifically investigate MGP2–10 from G. morsitans , the secretory peptide and conserved region 1 appear to be largely under negative selection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous examination of mammalian milk proteins revealed that discrete, specific sections of each gene are subject to neutral, negative or positive selection [32] . Using a similar MEGA-based analysis to specifically investigate MGP2–10 from G. morsitans , the secretory peptide and conserved region 1 appear to be largely under negative selection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Under the FEL method, posterior probabilities cutoffs were set at 95, which is equivalent to a p-value of 0.05 for the site-specific detection of codons under positive or negative selection. Analysis of specific regions of the MGP2–10 coding regions was conducted using MEGA5 according to previous milk protein studies [32] and individual regions were based upon protein coding regions with high or low levels of amino acid homology.…”
Section: Methodsmentioning
confidence: 99%
“…The Dasyuridae (carnivorous marsupials) have a minimally invasive (endotheliochorial) placenta, termed the marsupial yolk sac placenta, which forms once the shell coat ruptures in the last third of pregnancy (Renfree et al, ). Marsupials have a low maternal physiological investment during gestation when compared to that of many eutherian mammals, and marsupials have an extended lactation period (Pharo et al, ). Characterisation of desmosome expression in the uterine epithelium of marsupials during pregnancy will thus allow us to assess the generality of plasma membrane changes during pregnancy across mammalian species with similar placenta types and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that devils and wallabies are recruiting different proteins to fulfil the amino acid requirements of their PY, or that the differences in expression are due to additional functions of these proteins, for example several of these proteins are believed to play an immune role. ELP is likely to be a protease inhibitor, acting to prevent Ig degradation in the gut of the young ( Pharo et al, 2012 ) while β -lactoglobulin can be digested into anti-bacterial peptides in the gut ( Jenness, 1986 ; Pellegrini et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%